PENJATUHAN PUTUSAN PIDANA TERHADAP PERKARA PENIPUAN PROYEK PEMBANGUNAN AMENITAS KAWASAN PARIWISATA DI KABUPATEN PESISIR BARAT (Studi Putusan Nomor 17/Pid.B/2022/PN.Tjk). - Harimurti, Pangestika Raras; Seregig, I Ketut; Ramadan, Suta (IBLAM LAW REVIEW, 2024)
Fraud cases are a crime that has recently been frequently reported in newspapers, magazines and other mass media and has experienced quite a serious increase. Article 378 of the Criminal Code states that a person who commits a crime of fraud is threatened with a maximum prison sentence of 4 years. The issues that will be discussed in this issue are, Factors that Cause Perpetrators to Commit Criminal Acts of Fraud on Tourism Area Amenity Development Projects in Pesisir Barat Regency based on Decision Number 17/Pid.B/2022/PN.Tjk and How Criminal Decisions Are Handed Down in Cases of Criminal Project Fraud Development of Tourism Area Amenities in Pesisir Barat Regency based on Decision Number 17/Pid.B/2022/PN.Tjk. The research method used is a normative juridical and empirical approach, using secondary and primary data, obtained from literature studies and field studies, and data analysis using normative juridical analysis. The results of the research are factors in the occurrence of criminal acts of fraud using the financing method, namely due to several factors such as the defendant's lack of understanding of religion, apart from internal factors, there are factors that influence the defendant in committing fraud, such as environmental conditions and the condition of the defendant's residence which supports the occurrence of the crime. This, the defendant's low education and economic conditions were also very influential in the occurrence of this crime